Extranodal NK/T lymphoma diagnosed as refractory orbital cellulitis - Tito-Eusebio, Karyn Diana (2021)
A 60-year-old male, with a family history of a deceased brother diagnosed with nasal-type Natural Killer/T cell lymphoma (LNKTE), presented a clinical picture compatible with left orbital cellulitis and, subsequently, deterioration of general condition and liver failure. Without adequate response to antibiotics, eyelid biopsy revealed an LNKTE. He was treated with chemotherapy and died a month after diagnosis.